Patrick Moore's story of the earth - Moore, Patric (Philips London, 1991)
The history of planet Earth from its beginning as a cloud of dust and gas, explains how it moves through space, how the oceans and continents developed, and how life evolved from simple amoeba to dinosaurs and other animals, including humans.